Transcriptomic Changes of Piscirickettsia salmonis During Intracellular Growth in a Salmon Macrophage-Like Cell Line - Zúñiga, Alejandro; Aravena, Pamela; Pulgar, Rodrigo; Travisany, Dante; Ortiz-Severín, Javiera; Chávez, Francisco P.; Maass, Alejandro; González, Mauricio; Cambiazo, Verónica (Frontiers in Cellular and Infection Microbiology, 2020)
Piscirickettsia salmonis is the causative agent of Piscirickettsiosis, a systemic infection of salmonid fish species. P. salmonis infects and survives in its host cell, a process that correlates with the expression of virulence factors including components of the type IVB secretion system. To gain further insights into the cellular and molecular mechanism behind the adaptive response of P. salmonis during host infection, we established an in vitro model of infection using the SHK-1 cell line from Atlantic salmon head kidney. The results indicated that in comparison to uninfected SHK-1 cells, infection significantly decreased cell viability after 10 days along with a significant increment of P. salmonis genome equivalents. At that time, the intracellular bacteria were localized within a spacious cytoplasmic vacuole. By using a whole-genome microarray of P. salmonis LF-89, the transcriptome of this bacterium was examined during intracellular growth in the SHK-1 cell line and exponential growth in broth. Transcriptome analysis revealed a global shutdown of translation during P. salmonis intracellular growth and suggested an induction of the stringent response. Accordingly, key genes of the stringent response pathway were up-regulated during intracellular growth as well as at stationary phase bacteria, suggesting a role of the stringent response on bacterial virulence. Our results also reinforce the participation of the Dot/Icm type IVB secretion system during P. salmonis infection and reveals many unexplored genes with potential roles in the adaptation to intracellular growth. Finally, we proposed that intracellular P. salmonis alternates between a replicative phase and a stationary phase in which the stringent response is activated.